PENERAPAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SDN 8 DURI BARAT KECAMATAN MANDAU KABUPATEN BENGKALIS - Permata Puti Baydar; Mahmud Alpusari; zairul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was carried out because of low learning value of fifth grader students in Math subject  of SD Negeri 8 Duri Barat. Among 20 Students, 6 students (30%) reached the standard of completeness while the students could not reach the standard is 14 students (70%) with average 53,50. The purpose of this study is to increase the fifth grader students’ outcome in Math subject  of SD Negeri 8 Duri Barat   with the application of Indonesia Realistic Mathematic Education (PMRI). The results obtained by the average value of the basic score 53,50  in the first cycle increased by 12,25 to 65,75. In the second cycle the average value of students also increased as much as 28 becoming 81,50. On the basis of completeness score of Math subject, student learning outcomes is 30% (not complete). After the teacher was applying the Application of Indonesia Realistic Mathematic Education (PMRI) in the first cycle the classical completeness increase becoming 40 % (not complete), In the second cycle the classical completeness that have gotten by students increased becoming 80%. Teacher’s activity at the first meeting is 50% in enough category level. The second meeting increased becoming 75% in good category level. In the second cycle increased up to 95% in very good category level. In the second meeting of second cycle, the teacher’s activity increased becoming 100% in the very good category level. The students’ activity in the cycle I of first meeting got 50% percentage in enough category level. The second meeting of the first cycle becoming 60% in enough category. At the first meeting of the second cycle of student activity increased to 75% in good category, and the second meeting of the second cycle increased again to 90% with a very good category. Key Words : Indonesian Realistic Mathematic Education, learning outcomes mathematic.